Genotypic and Antimicrobial Characterisation of Propionibacterium acnes Isolates from Surgically Excised Lumbar Disc Herniations. (28th August 2013) - Rollason, Jess; McDowell, Andrew; Albert, Hanne B.; Barnard, Emma; Worthington, Tony; Hilton, Anthony C.; Vernallis, Ann; Patrick, Sheila; Elliott, Tom; Lambert, Peter
Abstract : The anaerobic skin commensal Propionibacterium acnes is an underestimated cause of human infections and clinical conditions. Previous studies have suggested a role for the bacterium in lumbar disc herniation and infection. To further investigate this, five biopsy samples were surgically excised from each of 64 patients with lumbar disc herniation. P. acnes and other bacteria were detected by anaerobic culture, followed by biochemical and PCR-based identification. In total, 24/64 (38%) patients had evidence of P. acnes in their excised herniated disc tissue. Using recA and mAb typing methods, 52% of the isolates were type II (50% of culture-positive patients), while type IA strains accounted for 28% of isolates (42% patients). Type III (11% isolates; 21% patients) and type IB strains (9% isolates; 17% patients) were detected less frequently. The MIC values for all isolates were lowest for amoxicillin, ciprofloxacin, erythromycin, rifampicin, tetracycline, and vancomycin (≤1mg/L). The MIC for fusidic acid was 1-2 mg/L. The MIC for trimethoprim and gentamicin was 2 to ≥4 mg/L. The demonstration that type II and III strains, which are not frequently recovered from skin, predominated within our isolate collection (63%) suggests that the role of P. acnes in lumbar disc herniation should not be readily dismissed.